2021
DOI: 10.1002/cjce.24245
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sweet whey permeate utilization on Tetradesmus obliquus growth and β‐galactosidase production

Abstract: The practicability of culturing microalgae in mixotrophic mode using sweet whey permeate (SWP), a highly perishable by‐product stream from cheese manufacturing, is evaluated for microalgal growth and β‐galactosidase production. This study is conducted with Tetradesmus obliquus, species known for their ability to adapt to various conditions with different carbon sources. The influence of pure lactose, the primary carbon source of SWP, is first surveyed. Partial substitutions of the basal culture medium with SWP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…During mixotrophic cultivation, both investigated microalgae effectively utilized cheese whey as a source of organic carbon, aligning with previous studies (Girard et al 2014 ; Pereira et al 2019 ; Tharani and Ananthasubramanian 2020 ; Bentahar and Deschênes 2022 ). In this nutritional mode, microalgal cells benefit from both inorganic and organic carbon sources, promoting simultaneous growth and the production of certain metabolites (Gomaa and Yousef 2020 ; Gomaa and Ali 2021 ).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…During mixotrophic cultivation, both investigated microalgae effectively utilized cheese whey as a source of organic carbon, aligning with previous studies (Girard et al 2014 ; Pereira et al 2019 ; Tharani and Ananthasubramanian 2020 ; Bentahar and Deschênes 2022 ). In this nutritional mode, microalgal cells benefit from both inorganic and organic carbon sources, promoting simultaneous growth and the production of certain metabolites (Gomaa and Yousef 2020 ; Gomaa and Ali 2021 ).…”
Section: Discussionsupporting
confidence: 87%
“…This mechanism has been previously confirmed in various microalgae, including T. obliquus and Cyanothece sp. (Suwal et al 2019 ; Zanette et al 2019 ; Chenebault et al 2020 ; Bentahar and Deschênes 2022 ). A detailed comparison of the growth and biochemical composition of the investigated microalgae in relation to previous studies regarding mixotrophic cultivation using cheese whey is listed in Table S4.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the metabolic versatility of this microalga species, no supplementation of the permeate was required. Other studies (Bentahar & Deschênes, 2022; Bentahar et al., 2019) have examined the effects of integrating various permeates into the growth media for microalgae Tetradesmus obliquus . Results showed that both sweet and acid WP addition could enhance the growth and β‐galactosidase production of this microalgae; however, acid WP may be preferable due to the higher ammonium and organic nitrogen contents (Bentahar & Deschênes, 2022).…”
Section: Indirect Applications (Lactose Derivative and Ingredients)mentioning
confidence: 99%
“…Other studies (Bentahar & Deschênes, 2022; Bentahar et al., 2019) have examined the effects of integrating various permeates into the growth media for microalgae Tetradesmus obliquus . Results showed that both sweet and acid WP addition could enhance the growth and β‐galactosidase production of this microalgae; however, acid WP may be preferable due to the higher ammonium and organic nitrogen contents (Bentahar & Deschênes, 2022). In addition, studies have demonstrated the ability of this microalgae, T. obliquus , to produce GOS in unsupplemented WP (Suwal et al., 2019), which may provide another future avenue for research.…”
Section: Indirect Applications (Lactose Derivative and Ingredients)mentioning
confidence: 99%